Bio-inspired hierarchical design of composite T-joints with improved structural properties. (February 2015) - Burns, L.; Mouritz, A.P.; Pook, D.; Feih, S.
Abstract: The biological principle of hierarchical (multi-scale level) design was used at the structural and laminate levels to design a novel carbon/epoxy T-joint with improved structural properties for potential use in light-weight aircraft structures. The bio-inspired structural modification mimics tree branch–trunk joints by embedding the stiffener flange into skin plies. This design concept results in increased fracture toughness due to crack branching and deflection. Simultaneously, bio-inspired ply angle optimisation was used to mimic the tailored arrangement of cellulose micro-fibrils observed in the wood cells contained within tree branch joints. The optimisation procedure minimises the interlaminar stress concentration in the T-joint radius bend and increases strength while maintaining similar global laminate stiffness properties. The hierarchical joint resulted in a significantly improved tensile strength compared to a conventionally designed T-joint. The new design additionally exhibited higher absorbed strain energy to failure load for bending and tension loading. Additionally, the hierarchical T-joint had a significantly reduced critical joint cross-sectional area (weight) due to the embedded design.